Role of Green Macro-Alga Enteromorpha Intestinalis in its Free and Immobilized State to Remove Copper Ions from Aqueous Medium - Al-Atbee , Rehab S.K.; Al-Bidhani , Mariam F.; Al-Mousawi, Nida J. (Mesopotamian Journal of Marine Sciences, 2025)
Heavy metals presence in industrial effluents may be a significant source of pollution that leads to considerable environmental issues. In the present work, the potential adsorptive behavior of algal cells Enteromorpha intestinalis for copper ions removal from aqueous medium has been studied in the states of alginate-immobilized algal cells and free algal cells. The impact of initial copper concentrations (5, 10 and 15) mg/l, contact time ranging from 0– 8 days has been studied at temperatures 25 °C, pH 7± 2 and agitation speed of 120 rpm. The algae achieved the highest efficiency at an initial concentration of 5 mg/l, reaching 74.49% on the fourth day of the experiment when treated with alginate-immobilized algae. In contrast, the free algae recorded a removal rate of 66.51% on the second day of the experiment. The alginate beads, on the other hand, achieved the lowest removal rate at the same concentration, reaching 38.75% on the second of the experiment. The analysis of the biosorption process using scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) before and after process showed that copper ions were primarily biosorped onto the algae cells surface